(2,2′-Dimethyl-4,4′-bi-1,3-thiazole-κ(2) N,N′)bis(thiocyanato-κS)mercury(II) - Safari, Nasser (International Union of Crystallography, 2009)
The Hg(II) atom in the title compound, [Hg(SCN)(2)(C(8)H(8)N(2)S(2))], is chelated by the bidentate heterocycle through the N atoms and is coordinated by the S atoms of two thiocyanate anions, resulting in a considerably distorted tetrahedral coordination geometry.